Investment under uncertainty and time-inconsistent preferences☆ - GRENADIER, S; WANG, N (Journal of Financial Economics, 2007)
While standard real options models assume that agents possess a constant rate of time preference, there is substantial evidence that agents are impatient about choices in the short term but are patient when choosing between long-term alternatives. We extend the real options framework to model the investment-timing decisions of entrepreneurs with time-inconsistent preferences. The impact on investment-timing depends on such factors as whether entrepreneurs are sophisticated or naive in their expectations regarding their future time-inconsistent behavior, and whether the payoff from investment occurs all at once or over time. The model is extended to the case of a competitive equilibrium.